FACILITY OF BIOGAS PRODUCTION IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
According to increasing of prices for energy resources, increasing interest for renewable energy resources. As one of the most profitable is biogas production. In this paper is presented potential of biomass for biogas production. It is presented possibility to produce biogas and energy from different recourses and total 156,9 million m3/year. For development of biogas production is necessary financial support, increasing of research works and education.